Enhancing Career Readiness of Hospitality Management Students through English Communication Skills and Project-Based Learning in Higher Education - Feri Ferdian; Yulia Efnawati; Eka Mayasari; Vischa Mansyera Pratama (Departemen Pariwisata Universitas Negeri Padang, 2025)
The study aimed to examine the influence of English communication skills on career readiness among hospitality management students, as well as the moderating role of Project-Based Learning (PJBL) in this relationship. The population in this study consisted of higher education students at Universitas Negeri Padang. Data collected from 108 valid respondents were analyzed using statistical tests, including correlation and moderation regression analysis. The findings revealed that English communication skills positively and significantly influence career readiness among hospitality management students. Furthermore, the implementation of Project-Based Learning (PJBL) was found to have a significant moderating effect on the relationship between English communication skill and career readiness. However, the interaction effect was negative, indicating that a higher level of Project-Based Learning (PJBL) implementation slightly weakens the direct influence of English communication skills on students’ career readiness. These findings provide several important theoretical and practical implications for enhancing students’ career readiness in higher education, emphasizing the integration of communicative competence and experiential learning through Project-Based Learning (PJBL).